MOLECULAR DETECTION OF UREASE AND HEMOLYSINE GENES IN PROTEUS MIRABILIS BACTERIA ISOLATED FROM URINE OF RHEUMATOID ARTHRITIS PATIENTS IN NAJAF PROVINCE - Abbas Kareem Magdy; Fatima Ali Hamid; Yasmine Khudair Nasser; Ikhlas Kazim Awaid; Ayaat Abbas Jawad (Journal of Medical Genetics and Clinical Biology, 2024)
P. mirabilis bacteria have a significant role in causing urinary tract infection which can be defined as the inflammatory response of urothelium to bacterial invasion, which is usually associated with bacteriuria and pyuria. According to the suggestion that Proteus microbes could possibly be involved in the etiopathogenesis. Proteus mirabilis was the commonest bacteria isolated in this study 15 (51% ) followed by E. coli in 6 ( 20.4 ), Klibsiella spp.5 (17%) and Staphylococcus saprophiticus 3 (10.3%). All isolates of P. mirabilis appeared highest rate of resistance (100%) in the case of Cefotaxime, Amoxicillin, Ampicillin. And moderately resistance to Netilmicin (71.4% ). All isolates presented high sensitivity (100%) to Meropenem, Levofloxacin, and Ciprofloxacin. All isolates15 (100%) appeared the presence of urease and hemolysine genes by using PCR technique